The Role of the Family Companion Team (TPK) in Finding New Cases of Families at Risk of Stunting - Oktaviani, Ni Putu Wiwik; Adiputra, I Made Sudarma; Trisnadewi, Ni Wayan (Indonesian Journal of Global Health Research, 2023)
Increasing human resources is one of Indonesia's efforts to build a golden Indonesia in 2045. Stunting is the current nutritional issue that Indonesia is dealing with. The Indonesian government has created a national strategy to accelerate stunting reduction through families involving health workers known as the Family Companion Team (TPK). According to the results of the evaluation of stunting prevention programs, most local governments have been unable to implement activities to accelerate stunting reduction. This research aims to determine the role of the family companion team in finding new cases of families at risk of stunting. Data collection in this study was carried out using multiple random sampling techniques, distributing questionnaires to 62 TPK in the working area of Puskesmas II Blahbatuh, the inclusion criteria for this study were TPK who had been listed in the Regent's Decree (SK), domiciled in the working area of the puskesmas II Blahbatuh and willing to be a respondent. This research hypothesis test uses Chi square. The results of this study show that there is no significant relationship between the role of TPK in finding new cases of families at risk of stunting and a p value > 0.05. The family approach is a good strategic innovation in providing assistance to families at risk of stunting, but it is not optimal in identifying new findings.